Value-semantic component of the psychological and pedagogical culture of the personality of students from psychological and pedagogical classes - N. V. Grebennikova (Вестник университета, 2025)
The article analyses the importance of creating psychological and pedagogical classes and describes their main goals. One of the results of the functioning of psychological and pedagogical classes is the development of psychological and pedagogical culture, which is identified within the framework of pedagogical science. The researchers defined it as the psychological culture of the teacher, but the expansion of understanding and the transition to educational psychology will allow for the inclusion of research and work on the development of the psychological and pedagogical culture of high school students (at the stage of pre-professional pedagogical training). Teaching in a psychological and pedagogical classroom is an important element of the pre-professional training of future teachers. Psychological and pedagogical culture is a complex education, the system-forming component of which, according to the author, is a value-semantic one. An empirical study is conducted aimed at identifying its features. The study includes the use of the following diagnostic techniques: “The system of life meanings” by V.Yu. Kotlyakov; “The test of life orientations” by D.A. Leontiev, adapted by E.N. Osin and N.V. Kosheleva; “The questionnaire of value orientations” by Sh. Schwartz, adapted by N.M. Lebedeva; mini-essay “My attitude to the teaching profession”. It is possible to note the existing differences in the research groups. It is revealed that the value of kindness, universalism, and safety is more significant for students of psychological and pedagogical classes. In addition, they strive more to achieve a high status in life, and there is a personal assessment in their value attitude towards the teaching profession. It is planned to introduce a course of pedagogy and psychology into the work of psychological and pedagogical classes, based on the formation of another person’s values, adequate setting of goals in life and the development of a value attitude towards the teaching profession.